Study of Trabekular Anatomic Structures on Biawak Water Bone (Varanus Salvator) - Haniaturizqia; Hasni, Amalia; Anwar, Miftahul (Proceeding International Conference on Science and Engineering, 2020)
Asian water lizards (Varanus salvator) is one of the species that is widespread in the region of South Asia and Southeast Asia, one of which is in the territory of Indonesia. One of the characteristics of water lizards is having a tail that serves to maintain the balance of his body when moving. This study aims to determine the anatomical structure of the trabeculae in the tailbone of the Asian water lizard (Varanus salvator). Trabeculae are derived from the aquatic biawaks tailbone, which is neutralized with chloroform and then dissected. The coccyx is taken and prepared for observation of trabecular anatomy by sanding part of the coccyx. Then observed the structural parts of the trabeculae using a microscope. Bone trabeculae can be seen as small, porous and porous tissue elements, which consist of trabekulated tissue. Based on the results of the study it can be concluded that the trabeculae of the monitor lizard’s tail bone consist of thin lattice elements and form spongy bones. The trabecular structure is thicker and denser to withstand external loading that is optimally regulated to withstand loads in functional activities such as jumping, running and for body balance. So that the dense trabecular structure of the monitor lizard’s tailbone can function optimally for the balance of the body of Asian water lizards in moving and doing activities.